A case study of an embedded system in prison to support individuals with learning difficulties and disabilities in the criminal justice system. (9th June 2015) - Kirby, Amanda; Saunders, Lisette
Abstract : Purpose: – The purpose of this paper is to describe first the rationale for an embedded process for learning difficulties and disabilities in the criminal justice system (CJS). This is followed by an example of how this approach has been delivered in one offender setting. The use of a novel computerised assessment tool is described, and the way it has been used to undertake the initial screening processes and provide person centred guidance for staff and the individuals. The bio-psychosocial approach to supporting individuals moving through the CJS is suggested as an approach that could be potentially used in other prisons settings. The paper also highlights some of the current challenges in doing so. Design/methodology/approach: – This paper presents a review of the currently literature to provide a rationale for the example of the embedded approach taken. Findings: – The approach, aligns to the challenges cited in much of the research. Practical implications: – The model presented can be used as a basis for potentially delivering such a system in other prisons settings and to highlight areas that remain contentious. Social implications: – The embedded model represents a bio-psychosocial approach to supporting individuals moving through the CJS so has important implications. Originality/value: – This is novel approach.